Effect of Tirofiban on new cerebral microbleeds after mechanical thrombectomy in patients with acute ischemic stroke - Sun,Yongdong (2021)
SUMMARY OBJECTIVE: The aim of this study was to analyze the effect of tirofiban on new cerebral microhemorrhage after mechanical thrombectomy in patients with acute ischemic stroke. METHODS: In total, 203 patients with acute ischemic stroke treated by mechanical thrombectomy in our department of neurology were enrolled as the research objects. The patients were divided into two groups: the patients who used tirofiban within 24 h after surgery were assigned to the study group (78 subjects), while patients who did not use tirofiban were assigned to the conventional group (125 subjects). Magnetic resonance imaging was used to detect new-onset cerebral microbleeds in patients with stroke after surgery. The National Institute of Health Stroke Scale, modified ranking scale, and activity of daily living scale were used to assess the prognosis of patients, and the general data and the occurrence of adverse effects between two groups were compared to comprehensively evaluate the efficacy and safety of tirofiban. RESULTS: The proportion of atrial fibrillation in the research group was significantly lower than that in the conventional group. The research group had a much lower rate of new-onset cerebral microbleeds than the conventional group (p<0.001). There was no significant difference in the proportion of adverse reactions between the two groups (p>0.05). CONCLUSION: The application of tirofiban in mechanical thrombectomy of patients with acute ischemic stroke has high safety, effectively reduces the occurrence of new cerebral microhemorrhage, and provides a guarantee for patient safety.